P446 Transcriptional and microbial biomarkers of response to anti-TL1A therapy in ulcerative colitis: the Phase 2a TUSCANY study. (15th January 2020) - Hassan-Zahraee, M; Ye, Z; Xi, L; Baniecki, M L; Li, X; Farin, W; Tibaldi, L; Allegretti, J R; Romatowski, J; Scherl, E J; Klopocka, M; Hyde, C; et al.
Abstract: Background: Tumour necrosis factor α-like ligand 1A (TL1A) acts as a synergistic cytokine that amplifies pro-inflammatory signals to increase T-cell, natural killer (NK) cell, and innate lymphoid cell production of cytokines, which are thought to be key drivers of inflammatory bowel disease (IBD) and intestinal fibrosis. The recent Phase 2a TUSCANY study demonstrated the efficacy of PF-06480605, a fully human immunoglobulin G1 monoclonal antibody targeting TL1A, in the treatment of participants with moderate to severe active Ulcerative Colitis (UC). Here, we present transcriptomic analysis of intestinal tissue biopsies and metagenomic analysis of the faecal microbiome to further evaluate the treatment effect of PF-06480605. Methods: The Phase 2a, open-label, multicentre, single-arm TUSCANY study (NCT02840721) evaluated the safety, tolerability and efficacy of PF-06480605 in participants with moderate to severe UC. Participants received 500 mg intravenous (IV) PF-06480605 every 2 weeks (Q2W) for a total of 7 doses, with a 14-week follow-up period. We performed RNA sequencing of colonic biopsies and metagenomic sequencing (>40 million reads per sample) of faecal samples taken prior to and after 12 weeks of therapy. Differential expression and cell subset deconvolution by CytoReason were used to identify genes and immune cells involved in response to therapy. Differential abundance analyses based on taxonomic profiling was performed using the GOTTCHA metagenome mapping algorithm to discover whether microbial taxa changed in response to treatment. Results: Tissue transcriptomic analysis identified a robust inhibition of adaptive (Th1, Th2 and Th17) and innate (macrophage) inflammatory pathways known to be associated with UC pathogenesis and a significant reduction in fibrosis-associated pathways (MMP3, MMP7 and MMP10). Transcriptomic responses were most pronounced in participants achieving endoscopic improvement (Mayo endoscopic subscore of ≤1). A candidate baseline gene signature was predictive of endoscopic improvement (area under the curve [AUC] 0.75; p -value = 0.03). Metagenomic analysis revealed a significant reduction in inflammatory pathobiont species ( S. salivarius, S. parasanguinis, and H. parainfluenzae ) following treatment. Conclusion: These results provide insight into the molecular and microbial mechanisms underlying the efficacy of anti-TL1A therapy for UC. We defined a baseline transcriptomic signature to predict response and a pathobiont treatment signature. These findings may enable the development of precision medicine strategies for anti-TL1A therapy in the treatment of intestinal inflammation.